Sistem informasi yang berkualitas di bpjs kesehatan Kota palembang - Venny Yusiana (Journal of Electrical Power Control and Automation (JEPCA), 2018)
Information systems have evolved along with technological developments that are very fast and proven in various activities. The existence of information systems that encourage performance, effectiveness and variety for various institutions. This research is to see the representation of quality information system at Health BPJS Palembang city based on the right variables. The results of the research indicate the value of the variables in the quality information system using the AMOS converter for the SEM method in the early stages.